Anatomical Comparison of Antennal Lobes in Two Sibling Ectropis Moths: Emphasis on the Macroglomerular Complex - Liu, Jing; He, Kang; Luo, Zong-xiu; Cai, Xiao-ming; Bian, Lei; Li, Zhao-qun; Chen, Zong-mao (Frontiers in Physiology, 2021)
Ectropis obliqua and E. grisescens are two sibling moth species of tea plantation in China. The male antennae of both species can detect the shared and specific sex pheromone components. Thus, the primary olfactory center, i.e., the antennal lobe, plays a vital role in distinguishing sex pheromones. To provide evidence for the possible mechanism allowing this distinction, in the present study, we compared the macroglomerular complex (MGC) of the antennal lobe between the males of the two species by immunostaining using presynaptic antibody and propidium iodide with antennal backfills as well as confocal imaging and digital 3D-reconstruction. The results showed that the MGC of both E. obliqua and E. grisescens contained five glomeruli at invariant positions between species. However, the volumes of the anterior-lateral glomerulus and posterior-ventral glomerulus differed between the species, which might be related to the differences in sensing sex pheromone compounds and their ratios between E. obliqua and E. grisescens. Our results provide an important basis for the mechanism of mating isolation between these sibling moth species.